EFEKTIVITAS KONSENTRASI EKSTRAK TEPUNG DAUN SIRSAK (Annona muricata L.) TERHADAP MORTALITAS ULAT GRAYAK JAGUNG Spodoptera frgiperda J. E. Smith DI LABORATORIUM - Desita Salbiah; Frida Indriatik (DINAMIKA PERTANIAN, 2025)
Spodoptera frugiperda is a pest that can cause the failure of young leaf formation in corn plants because it attacks the growing point of the plant. This pest can cause yield losses of 15%–73% in corn plants. Soursop leaf flour (Annona muricata L.) insecticide can serve as a safe alternative for controlling S. frugiperda. The study aims to determine an optimal concentration of soursop leaf flour (Annona muricata L.) extract that induces mortality in Spodoptera frugiperda J. E. Smith. This study was conducted at the Plant Pest Laboratory, Faculty of Agriculture, University of Riau, from July to September 2024, using a Completely Randomized Design (CRD) with five treatments and four replications. The treatment application consisted of soursop leaf flour extract at concentrations of 0 g·l⁻¹, 25 g·l⁻¹, 50 g·l⁻¹, 75 g·l⁻¹, and 100 g·l⁻¹ in water. Based on the results of administering several concentrations of soursop leaf flour extract to S. frugiperda, it was concluded that the concentration of soursop leaf flour extract at 100 g·l⁻¹ in water was an effective concentration against the mortality of Spodoptera frugiperda J. E. Smith larvae, as it caused a total mortality of 85% with an initial time of death of 21 hours after application. The appropriate concentration of soursop leaf flour extract to kill 50% of S. frugiperda larvae was 2.62%, or 26.2 g·l⁻¹ in water. The appropriate concentration to kill 95% of S. frugiperda larvae was 27.55%, or equivalent to 275 g·l⁻¹ in water.